A General Equilibrium Analysis of Inflation and Microfinance in Developing Countries - Daniel Müller (University of Basel, Center of Business and Economics (WWZ), 2013)
This paper analyses the welfare effects of microfinance and inflation in developing countries. Therefore, we introduce a moral hazard problem into a monetary search model with money and credit. We show how access to basic financial services affects households' decisions to borrow, to save and to hold money balances. The group lending mechanism of the microfinance institution induces peer monitoring, which in turn enables entrepreneurship. Our main result is that there exists an inflation threshold beyond which entrepreneurship collapses. We show that inflation affects the impact of microfinance on social welfare in a nonlinear way. The positive effect of microfinance is largest for moderate rates of inflation and drops substantially for inflation rates above the threshold.
Keywords: D82; E44; G21; O16; 330; Microfinance; Moral Hazard; Group Lending; Peer Monitoring and Monetary Policy; Mikrofinanzierung; Inflation; Moral Hazard; Geldpolitik; Wohlfahrtsanalyse; Allgemeines Gleichgewicht; Entwicklungsländer